Responses of a Maritime Antarctic lake to a catastrophic draining event under a climate change scenario - Izaguirre, Irina (2012)
The limnological features of Lake Boeckella, the main water body of Esperanza/Hope Bay (Antarctic Peninsula), were evaluated over a 16-year period, under a climate change context evidenced by the increasing air temperature trend reported for this region for the last 50 years. We analyzed the physicochemical and phytoplankton data of the lake obtained from 1991 to 2007 during the austral summers. At the beginning of January 2001, a sudden water level drop (~3 m) occurred in Lake Boeckella as a consequence of an extremely high water discharge to the sea. This was triggered by the progressive thawing of the permafrost in the basin of the system. After this disturbance, nutrients, conductivity, chlorophyll a (Chl a) and picoplankton density showed strong peaks. The pre-draining and post-draining periods showed signiWcant diVerences for most of the limnological variables analyzed. Secchi disk depth signiWcantly decreased throughout the study period, resulting in a thinner euphotic layer. Chrysophyceae and Volvocales dominated the >2 µm phytoplankton fraction in the lake, but from 2004 onwards, other small-sized eukaryotic algae (3?5 µm) also became very abundant. Autotrophic picoplankton showed a signiWcant peak during the summer when the water level decreased. A shift in their composition was observed through the study period: in 1998, picocyanobacteria were numerically dominant; from 2002 onwards, picoeukaryotes increased and became dominant in 2004. This study suggests that climate change may trigger the thawing of the permafrost in the catchments of Maritime Antarctic lakes, leading to catastrophic draining events, which favor natural eutrophication processes.